Studies on morpholigical and anatomical characters indicating C3 and C4 photosynthetic metabolism in the genus Boerhavia L.in Nigeria - Ajao, Abdulwakeel Ayokun-nun (Obafemi Awolowo University, 2019)
xiv,69